Value in Wayang Sukuraga as material for fiction texts in elementary school - Yoesrina Novia Vini Syafitri; Mamat Supriatna; Hazrul Affendi Mohmad Razali; Suciati Nur Apriyati (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2026)
Wayang Sukuraga is a traditional Sundanese art that visualizes human body parts as symbolic figures laden with moral values. This study aims to describe the values ​​contained in Wayang Sukuraga characters, such as Eyes, Ears, Mouth, Hands, and Feet, and their relevance as fictional text material in elementary schools. The method used is qualitative description with data collection techniques including interviews, observation, and documentation. The results of the study indicate that each Wayang Sukuraga character contains a strong moral message, including Eyes, which symbolize caution in judging, Ears, which depict the ability to filter information, mouth, which represents ethics in speaking, Hands, which reflect real work and actions, and Feet, which teach the right direction in life. These values ​​are educational, humanistic, and relevant for strengthening the character of elementary school students. In addition, Wayang Sukuraga has high potential as a source of inspiration in learning fictional texts, because the symbolism of its characters can be developed into imaginative stories rich in moral messages. Thus, Wayang Sukuraga is an effective cultural medium for instilling character values ​​through literacy learning in elementary schools.